A new species of Prionococcus (Hemiptera: Sternorrhyncha: Coccoidea: Coccidae) from Mexico, with a discussion of its affinities - Pellizzari, Giuseppina; Hodgson, Chris (Zootaxa, 2007)
The adult female, 1st-instar nymph, 2nd-instar female, 2nd-instar male, male puparium, prepupa, pupa, and adult male of a new species of Prionococcus Williams, Hodgson & Danzig, P. fontanai Pellizzari & Hodgson, are described and illustrated. Keys are given for the separation of the 3 species now in the genus Prionococcus and for separating the instars. The relationships of this genus within the family Coccidae are discussed.